Analisis SWOT Dalam Pengembangan Produk Usaha Rumahan Donut’s Amira - Wanti, Eny Trisno; Yunita, Tyna (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the SWOT (Strength, Weakness, Opportunity, Threat) analysis of the MSME (Micro, Small and Medium Enterprise)